ANALISIS DAN PENGARUH STAKEHOLDERS UNTUK PENINGKATAN KINERJA PUSAT PENELITIAN DAN PENGEMBANGAN GEOLOGI KELAUTAN (P3GL) BANDUNG - Hadi Wijaya; Juli Riauwati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Marine Geological Institute (MGI) of the Ministry of Energy and Mineral Resources (MEMR) becomes a government agency that implements Public Service Agency (PSA). This study aims to obtain the results of the analysis of the influence of stakeholders and their optimization efforts in improving the performance of PSA MGI for 2019.Data processing methods are influence - interest diagram and net-map toolbox. The influence - interest diagram will distinguish four types of stakeholders, namely promoters, defenders, latents and apathetics. The net-map analysis toolbox describes the relationship map as a framework for cooperation, and discussion as the substance. As a results, five new stakeholders were obtained or an increase of 112% who supported the implementation of activities and plans for future cooperation. The impact of optimizing stakeholders' activities is an increase in the performance of PSA MGI. From August to October 2019, additional work contracts were obtained, which increased by 185.4% in total from January until October 2019.